Christianity and the new spirit of capitalism - Tanner, Kathryn, 1957- (Yale University Press, 2019)
In his classic The Protestant Ethic and the Spirit of Capitalism, Max Weber famously showed how Christian beliefs and practices could shape persons in line with capitalism. In this significant reimagining of Weber's work, Kathryn Tanner provocatively reverses this thesis, arguing that Christianity can offer a direct challenge to the largely uncontested growth of capitalism. Exploring the cultural forms typical of the current finance-dominated system of capitalism, Tanner shows how they can be countered by Christian beliefs and practices with a comparable person-shaping capacity. Addressing head-on the issues of economic inequality, structural under- and unemployment, and capitalism's unstable boom/bust cycles, she draws deeply on the theological resources within Christianity to imagine anew a world of human flourishing. This book promises to be one of the most important theological books in recent years.